Actual problems of customs classification (on the example of Foreign Economic Activity Commodity Nomenclature of the Eurasian Economic Union) - Anna F. Algazina (Правоприменение)
The subject. The article is devoted to the main problem of customs classification on the example of Foreign Economic Activity Commodity Nomenclature (FEACN) of the EAEU. The purpose of the paper is to define the concept and meaning of classification of goods for customs purposes, the characteristics of the legal basis of FEACN, the identification of the features of cases challenging the decisions of customs authorities on the classification of goods in accordance with the EAEU FEACN. The hypothesis is to confirm or refute the relevance of the problems of customs classification for participants of foreign economic activity, and for customs authorities.The methodological basis for the study: general scientific methods (analysis, synthesis, comparison, description); private and academic (interpretation, formal‐legal).                  Results, scope. Features of classification of goods in customs declaration, in the implementation of customs control and in other cases regulated by the Customs Code of the EAEU. The classification of goods for customs purposes should be understood as the action taken by the declarant or customs authorities to classify goods as specific commodity items, sub‐ items and sub‐sub‐items of FEACN in accordance with the Basic rules of interpretation and the corresponding digital codes, which has legal significance in determining the amount of customs payments, in the application of non‐tariff regulation measures and in the frame‐ work of customs statistics for the purpose of summarizing data on goods moved.  The current FEACN of the EAEU was approved by the decision of the Council of the Eurasian Economic Commission. The FEACN used in the EAEU is derived from the Harmonized commodity description and coding system. In addition, the FEACN of the Commonwealth of Independent States, introduced after the conclusion of the relevant international legal agreement by the former Soviet republics in 1995, acts as the international basis of the EAEU FEACN.Since the size of customs payments depends on the HS code, the majority of disputes between participants of foreign economic activity and customs authorities arise in this category of cases, moreover, their number increases from year to year.Conclusions. As a result of the study, the concept and importance of classification of goods for customs purposes are defined, the legal basis of FEACN is characterized, the features of cases on challenging the decisions of customs authorities on the classification of goods in accordance with the EAEU FEACN are revealed. All of the above indicates the relevance of the problems of customs classification for participants of foreign economic activity, and for the customs authorities.